Intravitreal chemotherapy for vitreous disease in retinoblastoma revisited: from prohibition to conditional indications. Issue 8 (13th June 2012) - Munier, Francis L; Gaillard, Marie-Claire; Balmer, Aubin; Soliman, Sameh; Podilsky, Gregory; Moulin, Alexandre P; Beck-Popovic, Maja
Abstract : Background: Tumour control of vitreous seeds remains challenging owing to their resistance to radiation and systemic chemotherapy. Objective: To describe the short-term efficacy of intravitreal melphalan for vitreous disease in retinoblastoma using a new injection technique and dose. Methods: This study is a retrospective non-comparative review of 23 consecutive heavily pretreated patients (23 eyes) with active vitreous seeding and eligible for intravitreous chemotherapy (IViC). They received a total of 122 intravitreal injections of melphalan (20–30 μg) given every 7–10 days. The ocular status was objectively monitored under anaesthesia with fundus photography. Results: All patients are alive without evidence of extraocular spread (95% CI 82.19% to 100%). Concomitant treatments, including other chemotherapeutic modalities, were used until complete sterilisation of the retinal seeding source and subretinal seeds. Globe retention was achieved in 87% (20/23) of cases. All retained eyes were in complete remission after a median follow-up period of 22 months (range 9–31 months). The Kaplan–Meier estimate of ocular survival rates at 2 years was 84.14% (95% CI 62.48% to 95.28%). A localised peripheral salt-and-pepper retinopathy was noted in 10 eyes (43%) at the site of injection. Conclusions: This study reports the first clinically documented case series of patients with retinoblastoma treated with IViC. Despite a possible confounding effect of concomitant chemotherapy prescription using other routes of administration in four of the successfully treated eyes (20%), IViC achieved an unprecedented success rate of tumour control in the presence of vitreous seeding. Of note, none of the treated eyes required external beam irradiation to control the vitreous seeding. Further studies are required to assess IViC retinal toxicity and to better delineate its role in the management of retinoblastoma.